The Influence of Work Environment on Employee Performance at Astra Daihatsu Office, Alauddin Branch Makassar - Alwi Sandi; Andi Jam'an; Muhammad Akib (Economos : Jurnal Ekonomi dan Bisnis, 2025)
A conducive work environment is an important factor that can influence employee performance, as a safe, comfortable, and supportive atmosphere will encourage increased productivity and job satisfaction. This study aims to analyze the effect of the work environment on employee performance at the Astra Daihatsu Office, Alauddin Branch, Makassar. The research employs a quantitative approach with a survey method using a census technique, involving all 40 employees as respondents. Data were collected through observation, questionnaires, and documentation, and analyzed using validity tests, reliability tests, simple linear regression, and hypothesis testing with the help of SPSS version 21. The results show that the work environment has a positive and significant effect on employee performance, with a regression coefficient of 1.156 and a significance value of 0.000 (< 0.05). The coefficient of determination (R²) is 0.987, which means that 98.7% of the variance in employee performance is explained by the work environment, while the remaining 1.3% is influenced by other factors not examined in this study. These findings are consistent with previous research, which emphasized that a supportive, safe, and comfortable work environment contributes to increased productivity, discipline, and employee job satisfaction. The implication is that management needs to continuously improve both physical and non-physical aspects in the workplace, such as adequate lighting, harmonious relationships, and clear regulations, to ensure optimal employee performance and service quality.